The Role of Management Information Systems in Improving Islamic Education Services and Job Satisfaction in Madrasah - Ilham Yahya Romandoni; Prim Masrokan Mutohar; Imam Junaris; Sulistyorini Sulistyorini; Nur Efendi (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2025)
This study aims to analyze the use of Management Information Systems (MIS) in improving the quality of educational services and job satisfaction at Madrasah. The research employs a mixed methods approach with a sequential exploratory design, beginning with qualitative methods through observation, interviews, and documentation, followed by quantitative analysis using questionnaires distributed to 285 respondents. Qualitative data were analyzed using the Miles and Huberman interactive model, while quantitative data were examined through simple and multiple linear regression with SPSS. The qualitative findings indicate that MIS supports administrative efficiency, provides accurate data, and enhances service quality and job satisfaction across five key aspects: responsiveness, assurance, tangibles, empathy, and reliability. However, challenges such as limited infrastructure and user adaptability remain. Quantitatively, statistical tests show that MIS has a significant impact on both service quality and job satisfaction, as indicated by the F-value (2.679) exceeding the F-table value (2.410) with a significance level of 0.00 < 0.05. This study emphasizes the importance of a comprehensive and sustainable MIS implementation strategy to support the educational vision at Madrasah.